Framing sustainability: Alternative standards schemes for sustainable palm oil and South-South trade. (January 2019) - Higgins, Vaughan; Richards, Carol
Abstract: Agri-food sustainability standards developed through multi-stakeholder initiatives (MSIs) are an increasingly prominent form of governance that seeks to enhance participation by a broader range of stakeholders in defining and implementing sustainable agricultural practices. However, they have been characterised by social scientists as largely depoliticising and marginalising in their effects, leading to responses from stakeholder groups such as contestation, compromises and attempts to 'ratchet-up' existing standards. In this paper, we consider a response to MSI-developed sustainability standards that has been given limited attention in the literature to date – the development of alternative standards schemes and the framing of sustainability in the context of South-South trade relationships. Through a focus on the Indonesian and Malaysian Sustainable Palm Oil schemes (ISPO and MSPO), we apply Callon's writing on 'framing' to highlight how these schemes provide a response to the perceived stringent framing of sustainable palm oil in the Roundtable for Sustainable Palm Oil standards. Our analysis shows that the ISPO and MSPO are important in the creation of alternative frames for including smallholders who may not have the capacities or resources to participate in the RSPO. More significantly, the ISPO and MSPO provide a way of reframing sustainable palm oil that enables the palm oil sector in Indonesia and Malaysia to bypass the perceived challenges of RSPO certification and to balance existing price-based demands from their main export markets of India and China with future prospective sustainability demands in those markets. The paper concludes by arguing that sustainability schemes geared towards markets in the Global South need to be given greater scrutiny in terms of how they: (a) address the exclusion generated by MSI-developed certification schemes, and (b) reframe sustainability in ways that meet the current and emerging market requirements in South-South trade. Highlights: The Roundtable for Sustainable Palm Oil standards framing privileges Global North trade. Smallholder producers are not equipped to enter into the RSPO framing of sustainable palm oil. Callon's work is useful to address standards "framing". Nation-based standards re-framing addresses invisibilisation and exclusion. Alternative frames may broaden inclusion and South-South trade requirements but reduce standards.